2017
DOI: 10.1371/journal.pone.0172890
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of physical activity are independently associated with a lower incidence of diabetic retinopathy in Japanese patients with type 2 diabetes: A prospective cohort study, Diabetes Distress and Care Registry at Tenri (DDCRT15)

Abstract: We assessed the prospective association between baseline levels of physical activity (PA) and the incidence of newly developed diabetic retinopathy (DR) in patients with type 2 diabetes. Data from 1,814 patients with type 2 diabetes without DR were obtained from a Japanese diabetes registry at Tenri Hospital, Nara, Japan. To assess the independent correlations between baseline PA levels and newly developed DR, the participants were divided into five categories based on their PA levels. A Cox proportional hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…However, another cross-sectional study from Indonesian reported that PA was not correlated to vision-threatening DR, but had a protective effect on nephropathy, which is another common microvascular complication of diabetes [ 6 ]. Nevertheless, a recent longitudinal study in Japan showed that higher levels of PA were independently associated with a lower incidence of DR in patients with type 2 diabetes (HR = 0.63, 0.42–0.94; p<0.05) but this analysis was based on 2-years follow up data on 1,814 participants [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another cross-sectional study from Indonesian reported that PA was not correlated to vision-threatening DR, but had a protective effect on nephropathy, which is another common microvascular complication of diabetes [ 6 ]. Nevertheless, a recent longitudinal study in Japan showed that higher levels of PA were independently associated with a lower incidence of DR in patients with type 2 diabetes (HR = 0.63, 0.42–0.94; p<0.05) but this analysis was based on 2-years follow up data on 1,814 participants [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in type 2 diabetic patients found that higher levels of PA were associated with milder DR and less likelihood of DR onset; these studies were cross-sectional in design or limited by small sample size [ 6 8 ]. There is only one longitudinal study recently published, reporting a lower DR incidence in participants with higher PA levels, but this study was conducted in a small sample of the cohort during 2-year follow-up [ 9 ]. To the best of our knowledge, the longitudinal relationship between PA and progression to a vision-threatening stage of DR has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise mediates the effects of sleep on energy balance-related health outcomes [ 32 ]. Intensive physical activity levels were also independently associated with a lower incidence of diabetic retinopathy in Japanese patients with DM [ 33 ]. Muscle contractions of the lower extremities during exercise promote venous return to the heart [ 34 ], which helps to alleviate symptoms of nocturia and improves sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that AE may protect retinal cells from diabetes-induced injuries by inhibition of the underlying inflammatory and oxidative stress pathways (Dharmastuti et al, 2018). Loprinzi, Brodowicz, Sengupta, Solomon, and Ramulu (2014) In a cohort study in diabetic patients, Kuwata et al (2017) found that higher levels of AE are associated with a lower incidence of DR,…”
Section: Ae and Drmentioning
confidence: 99%